Catalyst and method for producing the same, water electrolysis device

CN116791130BActive Publication Date: 2026-11-03SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310190716.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-23
Publication Date
2026-11-03
Estimated Expiration
2043-02-23

AI Technical Summary

Technical Problem

Existing water electrolysis catalysts exhibit poor stability and activity during the OER process, especially Ru-based OER catalysts, which are prone to oxidation and deactivation in acidic environments, resulting in low water electrolysis reaction efficiency.

Method used

Boron carbon nitrogen compounds were used as supports to load ruthenium metal active materials. The modified supports improved the antioxidant and hydrophilic properties, and the active materials were adsorbed by negative valence atoms to form a stable catalyst structure.

Benefits of technology

It improves the chemical stability and catalytic activity of the catalyst, reduces the reaction overpotential, and enhances the electrolysis efficiency and service life of the water electrolysis device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116791130B_ABST
    Figure CN116791130B_ABST
Patent Text Reader

Abstract

The application discloses a catalyst and a preparation method thereof and a water electrolysis device. The catalyst comprises a carrier and an active material, the carrier is loaded with the active material, the carrier comprises a boron-carbon-nitrogen compound, and the active material comprises ruthenium metal. The boron-carbon-nitrogen compound improves the oxidation resistance of the carrier, and the nitrogen atom with a large electronegativity has more outer electrons, is closely combined with the Ru metal, is beneficial to keeping the active material in a low valence state and not easy to be deactivated, and thus improves the stability and catalytic effect of the catalyst. The preparation method of the catalyst comprises mixing raw materials and then performing sintering treatment in an inert atmosphere. The water electrolysis device contains the catalyst, and thus has high catalytic efficiency and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of electrochemical catalyst technology, specifically relating to catalysts and their preparation methods, and water electrolysis devices. Background Technology

[0002] Catalysts are materials used to accelerate the rate of chemical reactions. Catalysts generally contain a support and an active material, where the active material performs the catalytic action, and the support supports the active material. Taking the catalyst required for water electrolysis as an example, water electrolysis mainly consists of two parts: the oxygen evolution reaction (OER) at the anolyte and the hydrogen evolution reaction (HER) at the cathode. HER is a relatively simple 2-electron reaction, and hydrogen evolution catalysts are currently relatively mature. However, OER is a more complex 4-electron-proton coupled reaction with slow reaction kinetics, requiring a high potential environment and a strongly alkaline or strongly acidic environment, making the catalyst easily oxidized. Currently, commercially available acidic iridium-based OER catalysts still require a large reaction overpotential, around 10 mA / cm². 2 A potential exceeding 300mV is required under current conditions, which means that the water electrolysis reaction requires a high driving force. Therefore, OER (Oxygen Evolution Reactor) places extremely high demands on the activity and stability of the catalyst, making the oxygen evolution catalyst a major bottleneck restricting the development of hydrogen production through water electrolysis.

[0003] The catalytic activity of active materials in oxygen evolution reaction (OER) catalysts is generally reflected by the reaction overpotential; generally, the lower the reaction overpotential, the better the catalytic activity. Common active materials in OER catalysts include IrO2, Ru, and RuO2. Among them, IrO2 has the best activity and stability, but its yield is low and its price is high. Ru and RuO2 have high yields and low prices, and their OER activity is the strongest, but their stability is poor. During catalysis, they gradually oxidize to the high-valence state ruthenium RuO4, which is easily soluble in solution. In addition, although RuO2 is active, in acidic OER, lattice oxygen will participate in the reaction and be released, leading to structural collapse and deactivation.

[0004] Furthermore, OER catalysts require a support for the active material. The support is typically a carbon material with good conductivity, such as graphene, graphite, carbon nanotubes, and mesoporous carbon. However, graphene and graphite are easily oxidized to carbon dioxide at high potentials, especially in acidic OERs, leading to support loss and consequently affecting the catalyst's catalytic effect. Therefore, existing water electrolysis catalysts suffer from poor stability (short lifespan) and poor activity (poor catalytic effect), necessitating highly efficient and stable catalysts to accelerate the water electrolysis reaction and improve its efficiency. Summary of the Invention

[0005] The purpose of this application is to overcome the above-mentioned shortcomings of the prior art and provide a catalyst and its preparation method, as well as a water electrolysis device, to solve the problems of poor stability and poor activity of existing water electrolysis catalysts.

[0006] To achieve the aforementioned objectives, this application, in its first aspect, provides a catalyst. The catalyst comprises a support and an active material, wherein the support supports the active material, the support comprising a boron, carbon, or nitrogen compound, and the active material comprising ruthenium metal.

[0007] In this catalyst application, the support is a boron-carbon-nitrogen compound, which significantly improves the oxidation resistance and chemical stability of the support compared to carbon materials. Furthermore, boron-carbon-nitrogen compounds have higher hydrophilicity, facilitating contact between the active material and reactants and enhancing the catalytic effect. More importantly, the highly electronegative atoms in the support attract more outer electrons to achieve negative valence. These negative valence atoms become active sites for adsorbing the active material and help maintain the active material in a low valence state, making it less susceptible to oxidation and deactivation. Therefore, the support can enhance the activity of the active material, improving its stability and activity. This, in turn, improves the stability and activity of the catalyst.

[0008] In some embodiments, the molar ratio of boron:carbon:nitrogen in the boron carbon nitride compound is (2-20):(30-60):(30-60).

[0009] In some embodiments, the ruthenium metal has a nanoparticle structure with a particle size of 0.1 nm to 20 nm.

[0010] In some embodiments, the active material accounts for 5 wt% to 70 wt% of the catalyst by mass.

[0011] A second aspect of this application provides a method for preparing a catalyst. The preparation method includes the following steps:

[0012] A first mixture is obtained by mixing boron source, carbon source and nitrogen source in a certain proportion;

[0013] The first mixture is then subjected to a second mixing process with the active material source to obtain a second mixture;

[0014] The second mixture was sintered under an inert atmosphere to obtain the catalyst.

[0015] The catalyst preparation method of this application enables the integral sintering of the active material and the support. During the preparation process, the negatively valenced N active sites can tightly adsorb the active ions (Ru) from the active material source. 3+This method allows the active material to grow in situ on the support, improving the bonding strength and synergistic effect. Furthermore, the negatively valent nitrogen atoms in the support can anchor the active material, making it less susceptible to oxidation and deactivation, thus improving its stability and activity. Therefore, the prepared catalyst exhibits good chemical stability, high activity, and high catalytic efficiency. In addition, the process parameters of the catalyst preparation method in this application are controllable, resulting in stable catalytic performance.

[0016] In some embodiments, the first mixing process includes the following steps:

[0017] Boron source, carbon source and nitrogen source are dispersed in solvent to prepare a mixed solution;

[0018] The mixed solution was dried to obtain the first mixture.

[0019] In some embodiments, the drying process includes first performing rotary evaporation at 50°C to 80°C, followed by freeze drying.

[0020] In some embodiments, the second mixing process includes grinding the first mixture with an active material source.

[0021] In some embodiments, the sintering process includes a first sintering process at 200°C to 400°C, followed by a second sintering process at 500°C to 600°C.

[0022] In some embodiments, the boron source includes at least one of boric acid, boron trioxide, and borane.

[0023] In some embodiments, the carbon source includes at least one of melamine, glucose, and aniline.

[0024] In some embodiments, the nitrogen source includes at least one of melamine and urea.

[0025] In some embodiments, the boron source, carbon source, and nitrogen source are first mixed in a mass ratio of (2-20):(30-60):(30-60).

[0026] In some embodiments, the active material source includes at least one of ruthenium chloride, ruthenium nitrate, ruthenium acetylacetonate, and ammonium hexachlororuthenate.

[0027] In some embodiments, the first mixture is second-mixed with the active material source at a mass ratio of (1-10):(1-10).

[0028] A third aspect of this application provides a water electrolysis apparatus. The water electrolysis apparatus of this application includes a catalyst, which includes the catalyst described above or a catalyst prepared by the preparation method of this application.

[0029] The water electrolysis device of this application contains the catalyst described above, which endows the catalyst with good oxidation resistance, low reaction overpotential, stability, and activity. It can be used not only as a hydrogen evolution catalyst but also as an oxygen evolution catalyst in high-potential OERs, exhibiting good stability and activity in alkaline or strongly corrosive acidic environments. Therefore, the water electrolysis device of this application has high electrolysis efficiency and long service life. Attached Figure Description

[0030] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0031] Figure 1 This is a transmission electron microscope image of the catalyst in Example 1 of this application;

[0032] Figure 2 This is a transmission electron microscope image of the catalyst in Example 2 of this application;

[0033] Figure 3 This is a transmission electron microscope image of the catalyst in Example 3 of this application;

[0034] Figure 4 This is a transmission electron microscope image of the catalyst in Example 4 of this application;

[0035] Figure 5 The XRD patterns of the catalysts in Examples 1 to 4 of this application are shown below.

[0036] Figure 6 The XRD pattern of the catalyst in Example 8 of this application is shown.

[0037] Figure 7 This is a scanning electron microscope image of the first mixture in the preparation method of Example 1 of this application;

[0038] Figure 8 This is a scanning electron microscope image of the first mixture in the preparation method of Example 7 of this application;

[0039] Figure 9 Example 2 of this application uses a catalyst and RuO2 at 10 mA / cm 2 Timing potential diagram under current density;

[0040] Figure 10 The three catalysts in Example 2, Comparative Example 1, and Comparative Example 2 of this application were tested at 10 mA / cm. 2 Timing potential diagram under current density;

[0041] Figure 11 This is a flowchart of the catalyst preparation method of this application. Detailed Implementation

[0042] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0043] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.

[0044] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.

[0045] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.

[0046] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.

[0047] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a mass unit known in the chemical industry, such as μg, mg, g, or kg.

[0048] The terms "first" and "second" are used for descriptive purposes only, to distinguish objects, such as substances, from one another, and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. For example, without departing from the scope of the embodiments of this application, "first XX" may also be referred to as "second XX," and similarly, "second XX" may also be referred to as "first XX." Thus, features defined with "first" and "second" may explicitly or implicitly include one or more of that feature.

[0049] In a first aspect, embodiments of this application provide a catalyst. The catalyst of this application embodiment includes a support and an active material, wherein the support supports the active material, the support comprising boron, carbon, and nitride compounds, and the active material comprising ruthenium metal.

[0050] The inventors discovered in their research that the carrier in this application modifies the carbon material by replacing some of the carbon element (C) with boron (B) and nitrogen (N) to obtain boron-carbon-nitrogen compounds. Using these as a carrier significantly improves the carrier's antioxidant properties. The modified boron-carbon-nitrogen compounds retain strong antioxidant and chemical stability even under high potential, strong acid, or strong alkali environments, thus endowing the carrier in the catalyst of this application with strong antioxidant and chemical stability. The carrier material can be microscopically particulate with a porous structure or a nanosheet structure. The inventors also found that boron-carbon-nitrogen compounds have improved hydrophilicity compared to carbon materials, making them more conducive to sufficient contact between the active material and reactants, improving the catalytic effect; and the carrier still maintains good conductivity, ensuring electron flow and catalytic efficiency.

[0051] The inventors also discovered that after carbon materials are modified with B and N, due to the different electronegativity of B, C, and N atoms, the outer electrons of B, C, and N atoms in boron-carbon-nitrogen compounds will rearrange. This causes atoms with higher electronegativity to attract more outer electrons and achieve negative valence. These negative valence atoms become active sites for adsorbing active materials. These outer electrons help the active materials maintain a low valence state, making them less susceptible to oxidation and deactivation. Therefore, the carrier can enhance the activity of the active materials, improving their stability and activity. For example, in a CN bond, N has a high electronegativity, and the outer electrons of C atoms tend to shift to adjacent N atoms, making N more likely to be in a negative valence state, thus achieving the effect of maintaining a low valence state of the active materials and improving their stability and activity. For example, the electronegativity difference between B and N bonds is greater than that between CN bonds, so N atoms adjacent to B are more likely to achieve a negative valence, attracting more outer electrons and further improving the stability and activity of the active materials.

[0052] The active material includes ruthenium metal (Ru). Ru metal, as an active material, has a low reaction overpotential, good catalytic activity, and its price is relatively low compared to similar catalysts. More importantly, Ru is not easily oxidized and has good stability when supported on boron, carbon, and nitrogen compounds, thus maintaining its catalytic activity.

[0053] The active material can be loaded onto the support in a way that allows the active material to be uniformly dispersed and bound to the active sites on the support. This binding method makes the active material less prone to oxidation, improves its stability and activity, and allows it to better contact with the reactants, increasing the electron transfer rate, improving catalytic activity, and reducing the reaction overpotential.

[0054] In summary, the catalyst support in the embodiments of this application exhibits strong oxidation resistance and good chemical stability, and the active material easily maintains a low valence state, thus improving the stability and activity of the catalyst. Through research, the inventors have found that the catalyst in the embodiments of this application can be used not only as a hydrogen evolution catalyst in HER, but also as an oxygen evolution catalyst in high-potential OER. When used as an oxygen evolution catalyst, it exhibits excellent catalytic effect and stability not only in alkaline environments, but also in highly corrosive acidic environments, demonstrating good stability and activity.

[0055] In some embodiments, the molar ratio of boron:carbon:nitrogen in the boron carbon nitride compound can be (2-20):(30-60):(30-60).

[0056] The inventors discovered in their research that while modifying carbon materials with B and N to obtain boron-carbon-nitrogen compounds can improve the antioxidant properties of the support, excessively high B and N content can lead to a decrease in the conductivity of the support, affecting electron transport to some extent and thus impacting the catalytic efficiency of the catalyst. Therefore, a reasonable molar ratio of each element in the boron-carbon-nitrogen compound in the support is necessary. In the example, the molar ratio of B:C:N can be a typical but not limiting ratio such as (2, 5, 10, 15, or 20): (30, 40, 50, or 60): (30, 40, 50, or 60).

[0057] In some embodiments, the ruthenium metal morphology can be a nanoparticle structure, with a particle size ranging from 0.1 nm to 20 nm as tested. In exemplary examples, the particle size of the active material can be typical, but not limiting, sizes such as 0.1 nm, 0.2 nm, 2.85 nm, 3.82 nm, 4.28 nm, 5.25 nm, 10 nm, 15 nm, and 20 nm. Active materials with these particle sizes are easily and sufficiently dispersed and bound to the support, and can fully contact the reactants, thereby facilitating the catalytic effect of the active material.

[0058] In some embodiments, the active material accounts for 5 wt% to 70 wt% of the catalyst by mass. The inventors discovered that the proportion of active material cannot be too low, as this would result in a weak catalytic effect; nor can it be too high, as this would make it difficult for the support content to exert its loading effect, and the effect of boron, carbon, and nitrogen compounds in improving the stability and activity of the active material would also be difficult to achieve. In exemplary examples, the active material accounts for typical, but not limiting, percentages such as 5 wt%, 20 wt%, 35 wt%, 50 wt%, 60 wt%, and 70 wt% of the catalyst by mass.

[0059] Secondly, this application provides a method for preparing a catalyst. The preparation method includes the following steps:

[0060] S01: A first mixture is obtained by mixing boron source, carbon source and nitrogen source in a certain proportion;

[0061] S02: The first mixture is mixed with the active material source in a second mixing process to obtain a second mixture;

[0062] S03: The second mixture is sintered under an inert atmosphere to obtain a catalyst.

[0063] The catalyst preparation method in this application can integrally sinter the active material and the support to form the catalyst, which is the catalyst of the above embodiments. In the preparation method, the support contains N active sites with negative oxidation states (the N atoms bonded to B above attract more outer electrons), which can tightly adsorb the active ions (Ru) in the active material source. 3+ This method allows the active material to grow in situ on the support, improving the bonding strength and synergistic effect between the active material and the support, and enhancing the catalyst's stability. Furthermore, the negatively valence nitrogen atoms in the support can anchor the active material, making it less susceptible to oxidation and deactivation, thus improving its stability and activity. This two-stage mixing and then sintering method also results in more uniform dispersion of the active material and the support. Therefore, the prepared catalyst exhibits good chemical stability, high activity, and high catalytic efficiency. In addition, the process parameters of the catalyst preparation method in this application are controllable, and the catalyst's catalytic performance is stable.

[0064] Step S01:

[0065] Step S01 is the step of preparing the first mixture, namely the boron-carbon-nitrogen precursor.

[0066] In some embodiments, the boron source may include at least one of boric acid, boron trioxide, and borane.

[0067] In some embodiments, the carbon source may include at least one of melamine, glucose, and aniline.

[0068] In some embodiments, the nitrogen source may include at least one of melamine and urea.

[0069] These raw materials can provide the B, C, and N elements needed for boron, carbon, and nitrogen compounds, modifying carbon materials to produce carriers with good antioxidant properties and preventing the active materials from being oxidized. Furthermore, during the preparation process, atoms with high electronegativity can attract more outer electrons and achieve negative valence to adsorb Ru. 3+ Enhanced carrier and Ru 3+ The binding force; on the other hand, some raw materials have reducing properties, such as melamine and urea, which contain amino groups and can be used as reducing agents for subsequent Ru... 3+ It is reduced to Ru and becomes an active material.

[0070] In some embodiments, the boron source, carbon source, and nitrogen source can be first mixed in a mass ratio of (2-20):(30-60):(30-60). This ratio is reasonable for obtaining the proportion of the three elements in the boron-carbon-nitrogen compound, avoiding either too low a content of B and N elements resulting in insignificant modification effects, or too high a content of B and N elements affecting the conductivity of the carrier. In exemplary examples, the mass ratio of boron source:carbon source:nitrogen source can be a typical but not limiting ratio such as (2 or 5 or 10 or 15 or 20):(30 or 40 or 50 or 60):(30 or 40 or 50 or 60).

[0071] In some embodiments, the first mixing process may include the following steps:

[0072] Boron source, carbon source and nitrogen source are dispersed in solvent to prepare a mixed solution;

[0073] The mixed solution was dried to obtain the first mixture.

[0074] The first mixing process can be carried out in various ways. Here, solution mixing is used to mix and disperse the raw materials evenly. Then, drying can remove the solvent.

[0075] In some embodiments, the drying process may include first performing rotary evaporation at 50°C to 80°C, followed by freeze drying.

[0076] The inventors discovered in their research that after thoroughly mixing and dispersing the raw materials of the carrier in a solvent, and then drying them using conventional drying methods (such as oven drying), a first mixture was obtained. This mixture was then scanned using an electron microscope, as shown... Figure 8As shown, the first mixture exhibits large and uneven particle sizes. This is because conventional drying methods directly evaporate the solvent, transforming it from a liquid to a gaseous state. The gas-liquid interface has significant surface tension, making it easy for solute particles to agglomerate during this process. This is detrimental to forming a support with ideal particle size and stability, and thus hinders the improvement of the catalytic effect of the prepared catalyst. Therefore, in this embodiment, the inventors first used rotary evaporation to remove most of the water from the mixture of support raw materials, and then performed freeze-drying to freeze the solvent into a solid state, directly sublimating it into a gaseous state. The frozen solid solute maintains a relatively fixed position during sublimation, preventing agglomeration and facilitating the formation of uniform, smaller particles. The dried product was then scanned using an electron microscope, as shown... Figure 7 As shown, a first mixture with smaller and more uniform particle size can be obtained, which is beneficial for producing a carrier with a more suitable particle size and more uniform distribution, and for maximizing the loading effect of the carrier.

[0077] S02:

[0078] Step S02 is a step of thoroughly mixing the first mixture with the active material source for subsequent sintering to obtain the catalyst.

[0079] In some embodiments, the active material source includes at least one selected from ruthenium chloride, ruthenium nitrate, ruthenium acetylacetonate, and ammonium hexachlororuthenate. These active material sources can provide Ru... 3+ It is used to prepare Ru metal as an active material for catalyzing the electrolysis of water.

[0080] In some embodiments, the second mixing process includes grinding the first mixture with an active material source.

[0081] Through experimentation, the inventors discovered that the second mixing treatment of the first mixture and the active material source can be carried out in various ways. For example, it can be achieved by uniform mixing with a volatile solvent, or by mixing with a volatile solvent followed by multiple centrifugal washings to collect the solids, or by grinding both together. The inventors found that grinding can further reduce the particle size of the first mixture, preventing particle agglomeration and facilitating the uniform dispersion of the first mixture and the active material source. This results in a more uniform dispersion of the active material on the support in the prepared catalyst. Sufficient contact also allows for the full reduction of metal ions in the active material source, improving the catalytic effect of the prepared catalyst. Furthermore, this uniform dispersion fully utilizes the adsorption effect of the highly electronegative atoms in the first mixture, as mentioned above, enhancing the binding force between the two and tightly binding the active material ions to the first mixture. This ensures that during the growth of the active material during preparation, the active material can be stably bound to the support, improving the catalytic effect of the prepared catalyst.

[0082] In some embodiments, the first mixture and the active material source can be second-mixed at a mass ratio of (1-10):(1-10). Such a mass ratio can affect the ratio of support to active material in the resulting catalyst, avoiding situations where the support content is too low to provide adequate loading and prevent oxidation of the active material, and also avoiding situations where the support content is too high, affecting the active material content and reducing the catalyst's catalytic effect. In exemplary examples, the mass ratio of the first mixture to the active material source can be a typical, but not limiting, ratio such as (1, 3, 5, 7, or 10):(1, 3, 5, 7, or 10).

[0083] Step S03:

[0084] Step S03 involves sintering the second mixture to obtain the catalyst. The inert atmosphere has the effect of preventing the support and active material from being oxidized during the sintering process. The inert atmosphere can be a nitrogen or argon atmosphere.

[0085] In some embodiments, the sintering process may include a first sintering process at 200°C to 400°C, followed by a second sintering process at 500°C to 600°C.

[0086] The first sintering treatment removes impurities from the second mixture, improving raw material purity; promotes densification and crystal growth in the second mixture, reducing firing shrinkage; and activates the surface, thereby improving the overall sintering efficiency. The first sintering treatment can be performed at 200℃~400℃ for 20min~60min, with the temperature increased at a rate of 5℃ / min~20℃ / min to the corresponding temperature. A second sintering treatment is then performed to ensure sufficient reaction of the boron source, carbon source, nitrogen source, and active material source, yielding the catalysts described in the examples above. The sintering treatment should be thorough, for example, holding at 500℃~600℃ for 1h~10h. The first sintering treatment can be increased at a rate of 5℃ / min~20℃ / min to the corresponding temperature.

[0087] A water electrolysis apparatus includes a catalyst, which includes the catalysts described in the above embodiments or the catalysts prepared by the preparation methods described in the above embodiments.

[0088] The water electrolysis device of this application embodiment naturally includes necessary components such as an anode, cathode, water channel, oxygen channel, and hydrogen channel. Since the catalyst in the water electrolysis device of this application embodiment is the same as the catalysts in the previous embodiments, it possesses properties such as good oxidation resistance, low reaction overpotential, good stability, and good activity. Through experiments, the inventors have found that the catalyst of this application embodiment can be used not only as a hydrogen evolution catalyst in HER (hydrogen evolution reaction) but also as an oxygen evolution catalyst in high-potential OER (oxygen evolution reaction). When used as an oxygen evolution catalyst, it exhibits excellent catalytic effect and stability not only in alkaline environments but also in highly corrosive acidic environments. Therefore, the water electrolysis device of this application embodiment has high electrolysis efficiency and a long service life.

[0089] The catalysts and preparation methods of this application are illustrated below through several specific embodiments.

[0090] 1. Catalysts and preparation methods: Examples and comparative examples:

[0091] Example 1

[0092] This embodiment provides a catalyst and its preparation method. The catalyst includes a support and an active material. The support is a boron, carbon, and nitrogen compound, wherein the molar ratio of B:C:N is 3.72:39.26:54.38. The active material is ruthenium metal nanomaterial.

[0093] The catalyst preparation method in this embodiment includes the following steps:

[0094] S1: Weigh 1.26g of melamine and 0.62g of boric acid and dissolve them in 100mL of water. Stir at 95℃ until completely dissolved, then add to a rotary evaporator and rotary evaporate at 60℃ for 4h. After that, freeze dry to obtain the first mixture.

[0095] S2: Weigh 0.5g of the first mixture and 0.15g of ruthenium trichloride (RuCl3), mix them, and grind for 30 minutes until they are evenly mixed to obtain the second mixture;

[0096] S3: The second mixture is placed in a tube furnace and sintered at 300°C for 30 min under N2 atmosphere, and then sintered at 550°C for 6 h to obtain the catalyst.

[0097] Example 2

[0098] This embodiment provides a catalyst and its preparation method. The difference between this embodiment and the catalyst in Example 1 is that in step S2 of the preparation method, 0.15g of ruthenium trichloride is weighed instead of 0.25g of ruthenium trichloride.

[0099] Example 3

[0100] This embodiment provides a catalyst and its preparation method. The difference between this embodiment and the catalyst in Example 1 is that in step S2 of the preparation method, 0.15g of ruthenium trichloride is weighed instead of 0.35g of ruthenium trichloride.

[0101] Example 4

[0102] This embodiment provides a catalyst and its preparation method. The difference between this embodiment and the catalyst in Example 1 is that in step S2 of the preparation method, 0.15g of ruthenium trichloride is weighed instead of 0.5g of ruthenium trichloride.

[0103] Example 5

[0104] This embodiment provides a catalyst and its preparation method. The difference between this embodiment and the catalyst in Example 1 is that the molar ratio of B:C:N in the boron carbon nitrogen support is 2.72:42.68:48.09.

[0105] In step S1 of the preparation method, 1.26g of melamine and 0.31g of boric acid are weighed.

[0106] Example 6

[0107] This embodiment provides a catalyst and its preparation method. The difference between this embodiment and the catalyst in Example 1 is that the molar ratio of B:C:N in the boron carbon nitrogen support is 8.33:35.56:54.16.

[0108] In step S1 of the preparation method, 1.26g of melamine and 1.24g of boric acid are weighed.

[0109] Example 7

[0110] This embodiment provides a catalyst and its preparation method. The difference between the catalyst preparation method in this embodiment and the preparation method in Example 1 is that step S1 in this embodiment does not include the step of "adding to a rotary evaporator and evaporating at 60°C for 4 hours, followed by freeze-drying". Instead, it is replaced by the following step: adding to an oven and directly evaporating at 60°C to remove moisture, and then drying at 40°C until the moisture is completely removed.

[0111] Example 8

[0112] This embodiment provides a catalyst and its preparation method. The difference between the preparation method in this embodiment and the preparation method in Example 1 is that step S2 in this embodiment is replaced by the following step: Weigh 0.5g of the first mixture and 0.15g of ruthenium trichloride, mix them in 100mL of ethanol solvent and stir for 1 day, then wash them by centrifugation with water and ethanol multiple times, and collect the solid to obtain the second mixture.

[0113] Comparative Example 1

[0114] This comparative example provides a catalyst and its preparation method. The difference between this comparative example and Example 1 is that the support is sintered carbon.

[0115] The difference between the preparation method of this comparative catalyst and the preparation method of Example 1 is that 1.26g of melamine is weighed in step S1.

[0116] Comparative Example 2

[0117] This comparative example provides a catalyst. The difference between this comparative example and Example 1 is that the support is graphene.

[0118] 2. Characterization of the catalyst:

[0119] 2.1 TEM image of the catalyst

[0120] The catalysts prepared in Examples 1 to 8 were used to obtain corresponding images using a transmission electron microscope. The TEM images of the catalysts in Examples 1 to 4 are as follows: Figures 1 to 4 .

[0121] according to Figures 1 to 4 As can be seen, in the catalyst prepared by the method of this application embodiment, the active material is uniformly dispersed on the support, and the Ru metal particles are small in size and not easy to agglomerate, which makes the atom utilization rate of Ru metal high. Only a small amount of Ru metal loading is needed to have high catalytic activity.

[0122] 2.2 Catalyst XRD Images

[0123] The catalysts prepared in Examples 1 to 8 were tested using an X-ray diffractometer. The XRD results of the catalysts prepared in Examples 1 to 4 are shown in [Figure 1]. Figure 5 The catalyst prepared in Example 8 is shown in [reference needed]. Figure 6 .

[0124] according to Figure 5 As can be seen, in Examples 1 to 4, catalysts with boron carbon nitrogen compounds supported on Ru metal were successfully prepared, wherein Ru exists in a hexagonal stacked (hcp) manner, and XRD can also show that Ru is uniformly dispersed on the support.

[0125] according to Figure 6 As can be seen, Example 8 also successfully prepared a mixture of boron carbon nitride compound and Ru by stirring in an ethanol solution.

[0126] according to Figure 5 and Figure 6 In comparison, it can be seen that compared to Figure 5 XRD pattern of the catalyst, Figure 6The XRD peak broadening effect is not obvious, indicating that Ru agglomeration is relatively severe in the catalyst prepared by the method in Example 8. Therefore, the method of mixing and grinding the first mixture and the active material source in step S2 can better disperse the active material source and the first mixture uniformly, which is beneficial to obtaining uniformly dispersed active material and support, and ensuring the catalytic effect and stability of the catalyst.

[0127] 2.3 SEM image of the first mixture

[0128] The first mixture (carrier precursor) from step S1 of the preparation methods in Examples 1 and 7 were taken respectively, and corresponding images were obtained by scanning electron microscopy at the same magnification, as shown below. Figure 7 and Figure 8 As shown. Figure 7 The first mixture in the process has relatively smaller particle size and more uniform distribution. Therefore, compared with conventional direct evaporation drying, the first mixture (carrier precursor) obtained by drying the raw materials through rotary evaporation followed by freeze drying in step S1 has better quality.

[0129] 3. Catalyst performance testing:

[0130] 3.1 Catalyst performance testing:

[0131] The catalysts from Examples 1 to 8 and Comparative Examples 1 and 2 were used as oxygen evolution catalysts in OER. These oxygen evolution catalysts were placed in an oxygen-saturated 0.5 mol / L H2SO4 solution at 10 mA / cm². 2 The reaction overpotential of each oxygen evolution catalyst was tested using a dual potentiostat at the current density, and the results are shown in Table 1.

[0132] Table 1

[0133]

[0134] As can be seen from Table 1:

[0135] ①The reaction overpotentials of Examples 1 to 8 are all lower than those of Comparative Examples 1 and 2. Therefore, the catalysts in this application use boron carbon nitrogen compounds obtained by modifying carbon materials with B and N as supports, which reduces the OER reaction overpotential, improves the catalyst activity, and enhances the catalytic effect of the OER reaction.

[0136] ② Examples 1 to 4 were compared. As the proportion of active material in the catalyst increased, the reaction overpotential first decreased and then increased, indicating that the OER catalytic activity of the catalyst first increased and then decreased. This is because the activity initially increased with the increase in Ru metal atomic content, but after a certain point, the atomic utilization rate decreased, leading to a decrease in catalytic activity. This also shows that the proportion of active material has a reasonable range; it cannot be too low or too high, otherwise it will affect the catalytic effect of the catalyst.

[0137] ③ By comparing Example 1 with Examples 5 and 6, it can be seen that the catalyst can achieve good catalytic effect when the molar ratio of B, C and N in the support is within a certain range.

[0138] ④ Comparing Example 1 with Example 7, it can be seen that the use of rotary evaporation followed by freeze drying in step S1 of the preparation method will reduce the overpotential of the oxygen evolution reaction and improve the catalytic effect of the catalyst.

[0139] ⑤ Comparing Example 1 with Example 8, it can be seen that the grinding method used in step S2 of the preparation method reduces the overpotential of the oxygen evolution reaction, which can improve the catalytic effect of the catalyst.

[0140] 3.2 Catalyst stability test:

[0141] The catalyst from Example 2 and RuO2 were used separately in a water electrolysis device as OER catalysts for the anode oxygen evolution reaction, in an acidic environment with the same pH, at 10 mA / cm². 2 The reaction overpotential was tested at a current density and the time was recorded. The results are as follows: Figure 9 As shown;

[0142] from Figure 9 As can be seen, RuO2, when used directly as a catalyst, becomes unusable after only about 1 hour, losing its catalytic activity. In contrast, the catalyst in Example 2 has a longer lifespan compared to RuO2, demonstrating that Ru metal supported on boron carbon nitrogen compounds is less prone to oxidation and has improved stability.

[0143] The three catalysts from Example 2, Comparative Example 1, and Comparative Example 2 were used in a water electrolysis device as OER catalysts for the anode oxygen evolution reaction, in an acidic environment with the same pH, at 10 mA / cm². 2 The reaction overpotential was tested at a current density and the time was recorded. The results are as follows: Figure 10 As shown.

[0144] from Figure 10It can be seen that in Comparative Examples 1 and 2, which used sintered carbon and graphene as supports, the supports became unusable after only 3-6 hours. This indicates that catalysts using carbon materials as supports are easily oxidized and lose their activity. In contrast, the catalyst in Example 2 has a significantly longer service life, proving that boron carbon nitride compounds loaded with Ru metal are less prone to oxidation and have improved stability.

[0145] The above embodiments merely illustrate several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of this patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. A catalyst comprising a support and an active material, wherein the active material is supported on the support, characterized in that: The carrier comprises boron, carbon, and nitrogen compounds, and the active material comprises ruthenium metal; The preparation method of the catalyst includes the following steps: A first mixture is obtained by mixing boron source, carbon source and nitrogen source in a certain proportion; The first mixture is then subjected to a second mixing treatment with the active material source to obtain a second mixture; The second mixture was sintered under an inert atmosphere to obtain a catalyst; The first mixing process includes the following steps: The boron source, carbon source, and nitrogen source are dispersed in water to prepare a mixed solution; The mixed solution is first subjected to rotary evaporation at 50 ℃ to 80 ℃, and then freeze-dried to obtain the first mixture; the second mixing process includes grinding the first mixture with the active material source. The carbon source includes melamine.

2. The catalyst according to claim 1, characterized in that: The molar ratio of boron to carbon to nitrogen in the boron carbon-nitrogen compound is (2-20):(30-60):(30-60).

3. The catalyst according to claim 1 or 2, characterized in that: The ruthenium metal has a nanoparticle structure with a particle size of 0.1 nm to 20 nm.

4. The catalyst according to claim 1 or 2, characterized in that: The active material accounts for 5 wt% to 70 wt% of the mass of the catalyst.

5. The catalyst according to claim 1, characterized in that: The sintering process includes a first sintering process at 200 ℃ to 400 ℃, followed by a second sintering process at 500 ℃ to 600 ℃.

6. The catalyst according to claim 1, characterized in that: The boron source includes at least one of boric acid, boron trioxide, and borane; and / or The nitrogen source includes at least one of melamine and urea; and / or The boron source, carbon source, and nitrogen source are subjected to the first mixing treatment in a mass ratio of (2-20):(30-60):(30-60); and / or The active material source includes at least one of ruthenium chloride, ruthenium nitrate, ruthenium acetylacetone, and ammonium hexachlororuthenate; and / or The first mixture and the active material source are subjected to a second mixing treatment at a mass ratio of (1-10):(1-10).

7. A water electrolysis apparatus, comprising a catalyst, characterized in that: The catalyst includes the catalyst according to any one of claims 1 to 6.